Twisted intramolecular charge transfer (TICT) and twists beyond TICT: from mechanisms to rational designs of bright and sensitive fluorophores. (11th October 2021) - Wang, Chao; Chi, Weijie; Qiao, Qinglong; Tan, Davin; Xu, Zhaochao; Liu, Xiaogang
Abstract : The twisted intramolecular charge transfer (TICT) mechanism and twists beyond TICT have guided the creation of numerous bright and sensitive fluorophores. We reviewed the structure–property relationships of these dyes with representative examples. Abstract : The twisted intramolecular charge transfer (TICT) mechanism has guided the development of numerous bright and sensitive fluorophores. This review briefly overviews the history of establishing the TICT mechanism, and systematically summarizes the molecular design strategies in modulating the TICT tendency of various organic fluorophores towards different applications, along with key milestone studies and representative examples. Additionally, we also succinctly review the twisted intramolecular charge shuttle (TICS) and twists during photoinduced electron transfer (PET), and compare their similarities and differences with TICT, with emphasis on understanding the structure–property relationships between the twisted geometries and how they can directly affect the fluorescence of the molecules. Such structure–property relationships presented herein will greatly aid the rational development of fluorophores that involve molecular twisting in the excited state.